RETRACTED: Determination of the ability of a solar dryer based on a polyethylene ceramic composite to dry vegetables of various thicknesses - Rakhimov Rustam; Kuchkarov Akmal; Mukhtorov Dilmurod (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001